Kaji Komputational Karakteristik Aliran Air Gambut Pada Impeller Dan Volute Pompa Sentrifugal - Julianto, Arie; Kurniawan, Iwan; Osman, Kahar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In order to fulfil the need for higher water supply, water from the swamp may be used as an alternative. If one is to use the usual clean water centrifugal pump to operate in swampy condition, problem such as decreased in the pump head maybe encountered. This study aims to explore the modifications needed to counter the mentioned problem. Pumps with number of blades from 7 to 10 are tested to obtain optimum operating conditions. Peat water pump design is used in the modelling using Computational Fluid Dynamics technique. The results show that the head deviation difference between CFD and theoretical calculations is -5.85 % for clean water and 0.4% for peat water. For best operating conditions, the number of blade that generates the best result is 10 with head and efficiency of 70.23 m and 0.63 respectively.Keywords: Peat Water, Computational Fluid Dynamics, Centrifugal Pump, Impeller, Volute